Coleoptera Larval Fauna Associated with Termite Nests (Isoptera) with Emphasis on the “Bioluminescent Termite Nests” from Central Brazil - Cleide Costa; Sergio Antonio Vanin (Psyche: A Journal of Entomology)
Beetle larvae that inhabit termite nests present modifications that allow them to cohabitate with the termites. Some are physogastric and bear special glands and different setae all over their bodies, whereas others are not physogastric. Both kinds of larvae may be termite predators. Some species usually live in the nest cabbage pan, feeding on organic matter, mushrooms, and excrements or eating the nest walls and sometimes causing the nest to be destroyed. Other species live in superficial galleries of the nest and feed on preys that live outside. However, all interactions between these inquilines beetles and their termite hosts are very complex and still little understood. Emphasis was done to the bioluminescent termite nests from Central Brazil and for this reason general aspects of the bioluminescence related to the elaterid fireflies were also given. The adaptations to live in nest environment and functional categories of association of all beetle larvae we have studied, including those not bioluminescent, to termite nests are discussed in this work.